1980
DOI: 10.5014/ajot.34.11.715
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Interactions in Psychiatric Occupational Therapy–Some Inferences

Abstract: Five inferences drawn from research studies in the social sciences on the assessment of psychiatric ward atmospheres are presented as a frame of reference for psychiatric occupational therapists. The studies, based on a model stating that behavior results from the interaction of person and environment, suggest procedures for increasing successful treatment outcomes in occupational therapy. Such procedures include matching patients and staff to behavioral settings according to individual response traits and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Changes in the hospital milieu is a focus since the interaction between individual differences and the environmental setting can contribute to variance in an individual's behavioural responses and ultimately the treatment outcome (Reilly, 1966; Kannegieter, 1980). Changes in the hospital milieu is a focus since the interaction between individual differences and the environmental setting can contribute to variance in an individual's behavioural responses and ultimately the treatment outcome (Reilly, 1966; Kannegieter, 1980).…”
Section: The Milieumentioning
confidence: 99%
See 4 more Smart Citations
“…Changes in the hospital milieu is a focus since the interaction between individual differences and the environmental setting can contribute to variance in an individual's behavioural responses and ultimately the treatment outcome (Reilly, 1966; Kannegieter, 1980). Changes in the hospital milieu is a focus since the interaction between individual differences and the environmental setting can contribute to variance in an individual's behavioural responses and ultimately the treatment outcome (Reilly, 1966; Kannegieter, 1980).…”
Section: The Milieumentioning
confidence: 99%
“…Rehabilitation involves all those kinds of behaviour that go into achieving a social role in the family, on the job and in the community. Changes in the hospital milieu is a focus since the interaction between individual differences and the environmental setting can contribute to variance in an individual's behavioural responses and ultimately the treatment outcome (Reilly, 1966;Kannegieter, 1980). Reilly (1966) suggested that the occupational therapy treatment programme should include:…”
Section: The Milieumentioning
confidence: 99%
See 3 more Smart Citations